2020
DOI: 10.3390/agriculture10110490
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 1-Methylcyclopropene Treatment on the Fruit Quality of ‘Idared’ Apples during Storage and Transportation

Abstract: 1-Methylcyclopropene (1-MCP) is applied as an inhibitor of ethylene action, which is widely used in postharvest technology to prolong the shelf life of many fruits. The aim of the study was to assess the possibility to apply 1-MCP treatment to maintain the quality of ‘Idared’ apples for long-distance transportation. The studied apples were assessed in three groups: (I) 1-MCP postharvest treatment; (II) 1-MCP postharvest treatment with Modified Atmosphere Packaging (MAP) selected gas permeability bags; and (III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
(53 reference statements)
1
12
0
Order By: Relevance
“…Even the lowest concentration at a minimum number of applications, i.e., single application of 0.5 µL L −1 1-MCP, exhibited a significant effect on IEC and TA. These findings were supported by previous studies [20,34] that even a small amount of 1-MCP can efficiently control the IEC and maintain TA during storage. For most climacteric fruits, the minimum effective concentration of 1-MCP was known to be 1 µL L −1 [28].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Even the lowest concentration at a minimum number of applications, i.e., single application of 0.5 µL L −1 1-MCP, exhibited a significant effect on IEC and TA. These findings were supported by previous studies [20,34] that even a small amount of 1-MCP can efficiently control the IEC and maintain TA during storage. For most climacteric fruits, the minimum effective concentration of 1-MCP was known to be 1 µL L −1 [28].…”
Section: Discussionsupporting
confidence: 87%
“…To control ethylene, 1-methylcyclopropene (1-MCP) is used as an ethylene inhibitor [13][14][15]. Previous reports indicated that 1-MCP had excellent effects not only in suppressing ethylene action during storage but also in maintaining the quality of fruits such as fruit softening, fruit firmness, and TA [13,[16][17][18][19][20][21][22]. However, the apple has an extensive range of cultivars with different ripening rates, harvest standards, postharvest procedures, and storage periods [23].…”
Section: Introductionmentioning
confidence: 99%
“…Ambient temperature during transport and sale in tropical countries can significantly contribute to the loss of fruit quality. In the literature, a few reports raise issues describing changes in the content of phenolic compounds in apples stored in a controlled atmosphere technology or treated with 1-methylcyclopropene [14,23,26].…”
Section: Discussionmentioning
confidence: 99%
“…The studied fruit were the Idared cultivar apples obtained 23 October 2018, from the orchard in Julianów (51 • 46 N 20 • 49 E), in the Belsk Du ży district, which were afterwards stored until 2019. The studied apples were from the same orchard, same season and same harvesting, as studied previously [26], so the observations may be compared with those from the previous study.…”
Section: Studied Groupsmentioning
confidence: 99%
“…If applied immediately after harvesting and combined with cold storage, 1-MCP is indicated even as an affordable alternative to controlled atmosphere, to maintain the quality of fruits [25]. The studies conducted so far revealed that 1-MCP applied postharvest contributed to improved quality of Idared apples during 6 weeks of simulated long-distance transportation [26], but it was not studied if this period of transportation may be prolonged. Taking into account the current unpredictable global situation, which imposes taking into account the possible difficulties and planning adjustable solutions for international transportation [27], the aim of the present study was to assess the possibility to apply 1-MCP treatment to maintain the quality of Idared apples for long-distance transportation prolonged for 8 weeks.…”
Section: Introductionmentioning
confidence: 99%